Post thaw evaluation and fertility of bovine semen diluted in Biociphos plus and tris extenders - RAO, N KARUNAKARA; RAO, A SESHAGIRI; NAIDU, K SUBRAMANYAM; NAIDU, K VENUGOPAL; RAO, A MUTHA (The Indian Journal of Animal Reproduction, 2023)
A comparative study on post tliaw semen characteristics and fertility of Murrah and Jersey bull semen diluted with a new yolk free "Biociphos plus" and routinely used yolk containing "Tris" e>..1enders was undertaken. The variation in overall prefreeze motility was found to be significant (P<0.05) between the two diluents in both the breeds. Also significant difference was noticed in the post tliaw motility (P<0.0 1) and post tliaw acrosomal damage (P<0.05). Interestingly, Biociphos plus was found to be highly superior to Tris in arresting bacterial contamination of semen. However, the fertility rates between diluents did not differ much in both the breeds.